Teaching 'Ilm al-Ma'ani in Arabic Rhetoric: Goals, Content, Methodology, and Assessment - Farid , Edi Kurniawan; Zainullah, Ahmad (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2026)
Abstract: Balaghah is an important part of the Arabic language that we should not neglect. This is because the benefits of learning Balaghah are not only about cognitive aspects, but also include the development of emotional aspects and skills. Because Balaghah has both scientific and artistic aspects at the same time. Therefore, learning Balaghah is one of the ways to reveal the beauty and secrets of the language and develop the learner's personality. While The learning of 'Ilm al-Ma'ani, which is a branch of 'Ulumul Balaghah, it enhanches the learner's to adjust their speech by considering the interlocutor and the situation in which they speak. This study aimed to uncover principles of 'Ilm al-Ma'ani and provide essential guidelines for teaching it, that addopted from experts and scholars in the field of Bal?ghah, especially in 'Ilm al-Ma'ani. This research is a literature study whose data is taken from books, research, and journals in the field of Balaghah. Data collection uses documentation techniques and the data is analyzed using the interactive model method, namely data reduction, display, and deduction. The findings of this study are concepts related to Bal?ghah and its branchs, of which 'Ilm al-Ma'ani is a branch. Another key result is the identification of essential guidelines for teaching 'Ilm al-Ma'ani, which Balaghah's teachers—especially those focused on this field—must consider in order to achieve the goal of this science: literary appreciation and sensitivity. These guidelines include the principles of teaching 'Ilm al-Ma'ani, its objectives, content, methods, and evaluation.